The (ir)relevance of the NRU for policy making ; the case of Denmark - Marika Karanassou; Hector Sala; Pablo F. Salvador (Queen Mary University of London, Department of Economics, 2006)
We reconsider the central role of the natural rate of unemployment (NRU) in forming policy decisions. We show that the unemployment rate does not gravitate towards the NRU due to frictional growth, a phenomenon that encapsulates the interplay between lagged adjustment processes and growth in dynamic labour market systems. We choose Denmark as the focal point of our empirical analysis and find that the NRU explains only 33% of the unemployment variation, while frictional growth accounts for the remaining 67%. Therefore, our theoretical and empirical findings raise serious doubts as to whether the NRU should play a key instrumental role in policy making.
Keywords: E22; E24; J21; 330; Unemployment; Natural rate of unemployment; Labour market dynamics; Frictional growth; Chain reaction theory